Far from home: A multi-analytical approach revealing the journey of an African-born individual to imperial Rome. (June 2021) - Salesse, Kevin; Dufour, Élise; Balter, Vincent; Tykot, Robert H.; Maaranen, Nina; Rivollat, Maïté; Kharobi, Arwa; Deguilloux, Marie-France; Pemonge, Marie-Hélène; Brůžek, Jaroslav; Castex, Dominique
Highlights: First direct evidence for an African migrant born beyond the limes found in Rome. One of the few known cases of long-distance migration across the Roman Empire. Brings new information about the cosmopolitan character of the imperial capital. Individual US215/Mand1 underwent most likely a forced migration as a slave. Snapshot nature of the mass graves in the Saint Peters and Marcellinus catacombs. Abstract: Rome saw its number of foreign individuals increase considerably as the empire expanded. These foreigners arrived as either free persons or slaves from the newly conquered provinces and near-frontier zones and came to influence the whole life of the city. Yet relatively little is known about their life histories. In this study, we bring direct evidence for the first example of an African-born migrant, with an origin beyond the southern imperial border, discovered in Rome. Based on a multi-tissue sampling strategy including molar teeth and mandibular cortical bone, a multi-analytical approach including isotopic (δ 13 C, δ 15 N, δ 18 O, δ 34 S, 87 Sr/ 86 Sr), dental morphology (geometric morphometrics, nonmetric traits) and ancient DNA (mitochondrial DNA, Y chromosome) analyses allows reconstructing the journey and lifeway patterns of the individual US215/Mand1 buried in the mass grave from the catacombs of Saints Peter and Marcellinus. The successful isotopic and dental morphology analyses suggest that the individual was probably born in the vicinity of the Nile Valley or within the central Sahara Desert. Results also suggest a diachronic change of residence in the area during their early life. The way US215/Mand1 reached Rome is still hypothetical, although it seems likely that the individual could have undergone forced migration as a slave to the capital.